Marketing Communication Effect on Customer Relationship-A New Paradigm Shift in Customer Satisfaction: Evidence from Nigerian Airline Industry - Adebayo, Adeyemi Abdulwasiu (Universitas Indonesia Membangun (Inaba), 2024)
Due to competition that is evolving in Nigerian airline industry and the need to build relationship with customer has results in the aviation sector’s quest to device effective marketing communication elements to generate satisfaction. This study investigated the impact of marketing communication on customer relationships within selected airline companies in Lagos state, Nigeria. Employing a quantitative research design due to the infinite population size, the study utilized a survey method with questionnaires to collect primary data from domestic customers of the chosen airlines. The sample size of 246 was determined using Godden model, employing multistage sampling techniques. A total of 150 questionnaires were gathered for data analysis. Standard multiple regression was employed to analyze the data. The findings indicated that advertising showed a significant relationship with customer relationships (β = .227, t = 2.015, p < .011), and sales promotion also exhibited a positive and significant relationship with customer relationships (β = 0.412, t = 1.925, p = .005). The study concluded that implementing effective marketing communication elements such as advertising and sales promotion by airline management enhances the relationship between the firm and its customers by facilitating interaction between customers and airline service providers. The study recommends that airline service providers should formulate their communication strategies to raise awareness, stimulate interest and desire, and prompt actions among customers toward their services. This approach aims to establish robust customer relationships capable of enduring the dynamic business environment and enhancing customer satisfaction.